Answer:
Yes, The expressions 8a² - 4b + 7a² and 5(3a² - 2b) + 6b are equivalent
Explanation:
To answer the question you must simplify each expression, then compare them to find if they are equivalent or not
∵ The 1st expression = 8a² - 4b + 7a²
→ Add the like terms
∴ The 1st expression = (8a² + 7a²) - 4b
∴ The 1st expression = 15a² - 4b
∵ The 2nd expression = 5(3a² - 2b) + 6b
→ Multiply the bracket by 5
∴ The 2nd expression = 5(3a²) - 5(2b) + 6b
∴ The 2nd expression = 15a² - 10b + 6b
→ Add the like terms
∵ The 2nd expression = 15a² + (-10b + 6b)
∴ The 2nd expression = 15a² + -4b
→ Remember (+)(-) = (-)
∴ The 2nd expression = 15a² - 4b
∵ The 1st expression = The 2nd expression
∴ The two expressions are equivalent
∴ The expressions 8a² - 4b + 7a² and 5(3a² - 2b) + 6b are equivalent